Migrant Networks and Trade: The Vietnamese Boat People as a Natural Experiment - Christopher Parsons; Pierre-Louis Vézina (Institute for the Study of Labor (IZA), 2016)
We provide evidence for the causal pro-trade effect of migrants and in doing so establish an important link between migrant networks and long-run economic development. To this end, we exploit a unique event in human history, i.e. the exodus of the Vietnamese Boat People to the US. This episode represents an ideal natural experiment as the large immigration shock, the first wave of which comprised refugees exogenously allocated across the US, occurred over a twenty-year period during which time the US imposed a complete trade embargo on Vietnam. Following the lifting of trade restrictions in 1994, US exports to Vietnam grew most in US States with larger Vietnamese populations, themselves the result of larger refugee inflows 20 years earlier.
Keywords: F14; F22; 330; natural experiment; US exports; migrant networks